Inhalation exposure to three-dimensional printer emissions stimulates acute hypertension and microvascular dysfunction - Stefaniak, A.B.; LeBouf, R.F.; Duling, M.G.; Yi, J.; Abukabda, A.B.; McBride, C.R.; Nurkiewicz, T.R. (Toxicology and applied pharmacology, 2017)
Fused deposition modeling (FDM™), or three-dimensional (3D) printing has become routine in industrial, occupational and domestic environments. We have recently reported that 3D printing emissions (3DPE) are complex mixtures, with a large ultrafine particulate matter component. Additionally, we and others have reported that inhalation of xenobiotic particles in this size range is associated with an array of cardiovascular dysfunctions. Sprague-Dawley rats were exposed to 3DPE aerosols via nose-only exposure for ~3h. Twenty-four hours later, intravital microscopy was performed to assess microvascular function in the spinotrapezius muscle. Endothelium-dependent and -independent arteriolar dilation were stimulated by local microiontophoresis of acetylcholine (ACh) and sodium nitroprusside (SNP). At the time of experiments, animals exposed to 3DPE inhalation presented with a mean arterial pressure of 125±4mmHg, and this was significantly higher than that for the sham-control group (94±3mmHg). Consistent with this pressor response in the 3DPE group, was an elevation of ~12% in resting arteriolar tone. Endothelium-dependent arteriolar dilation was significantly impaired after 3DPE inhalation across all iontophoretic ejection currents (0–27±15%, compared to sham-control: 15–120±21%). Endothelium-independent dilation was not affected by 3DPE inhalation. These alterations in peripheral microvascular resistance and reactivity are consistent with elevations in arterial pressure that follow 3DPE inhalation. Future studies must identify the specific toxicants generated by FDM™ that drive this acute pressor response.